Pyruvate Dehydrogenase Kinase-mediated Glycolytic Metabolic Shift in the Dorsal Root Ganglion Drives Painful Diabetic Neuropathy - Rahman, Md Habibur (J Biol Chem, 2016)
The dorsal root ganglion (DRG) is a highly vulnerable site in diabetic neuropathy. Under diabetic conditions, the DRG is subjected to tissue ischemia or lower ambient oxygen tension that leads to aberrant metabolic functions. Metabolic dysfunctions have been documented to play a crucial role in the pathogenesis of diverse pain hypersensitivities. However, the contribution of diabetes-induced metabolic dysfunctions in the DRG to the pathogenesis of painful diabetic neuropathy remains ill-explored. In this study, we report that pyruvate dehydrogenase kinases (PDK2 and PDK4), key regulatory enzymes in glucose metabolism, mediate glycolytic metabolic shift in the DRG leading to painful diabetic neuropathy. Streptozotocin-induced diabetes substantially enhanced the expression and activity of the PDKs in the DRG, and the genetic ablation of Pdk2 and Pdk4 attenuated the hyperglycemia-induced pain hypersensitivity. Mechanistically, Pdk2/4 deficiency inhibited the diabetes-induced lactate surge, expression of pain-related ion channels, activation of satellite glial cells, and infiltration of macrophages in the DRG, in addition to reducing central sensitization and neuroinflammation hallmarks in the spinal cord, which probably accounts for the attenuated pain hypersensitivity. Pdk2/4-deficient mice were partly resistant to the diabetes-induced loss of peripheral nerve structure and function. Furthermore, in the experiments using DRG neuron cultures, lactic acid treatment enhanced the expression of the ion channels and compromised cell viability. Finally, the pharmacological inhibition of DRG PDKs or lactic acid production substantially attenuated diabetes-induced pain hypersensitivity. Taken together, PDK2/4 induction and the subsequent lactate surge induce the metabolic shift in the diabetic DRG, thereby contributing to the pathogenesis of painful diabetic neuropathy.